ANALYSIS OF FORMS OF OBSESSIVE COMPULSIVE DISORDER IN ADOLESCENTS - Khudaiberdieva, Dilorom (Журнал Педагогики и психологии в современном образовании, 2024)
This article is devoted to the analyzing the prevalence of obsessive-compulsive disorder in adolescents and assessing its severity at the ages of 10-11 and 15 – 16 . This period has been taken because it is called transitional, since at this time the child moves from a child’s model of behavior to an adult. In addition, during this period the teenager experiences serious physiological changes.